Endoplasmic reticulum stress and quality control in relation to cisplatin resistance in tumor cells - Mu, Wentao; Zhi, Yao; Zhou, Jianpeng; Wang, Chuanlei; Chai, Kaiyuan; Fan, Zhongqi; Lv, Guoyue (Frontiers in Pharmacology, 2024)
The endoplasmic reticulum (ER) is a crucial organelle that orchestrates key cellular functions like protein folding and lipid biosynthesis. However, it is highly sensitive to disturbances that lead to ER stress. In response, the unfolded protein response (UPR) activates to restore ER homeostasis, primarily through three sensors: IRE1, ATF6, and PERK. ERAD and autophagy are crucial in mitigating ER stress, yet their dysregulation can lead to the accumulation of misfolded proteins.Cisplatin, a commonly used chemotherapy drug, induces ER stress in tumor cells, activating complex signaling pathways. Resistance to cisplatin stems from reduced drug accumulation, activation of DNA repair, and anti-apoptotic mechanisms. Notably, cisplatin-induced ER stress can dualistically affect tumor cells, promoting either survival or apoptosis, depending on the context.ERAD is crucial for degrading misfolded proteins, whereas autophagy can protect cells from apoptosis or enhance ER stress-induced apoptosis.The complex interaction between ER stress, cisplatin resistance, ERAD, and autophagy opens new avenues for cancer treatment. Understanding these processes could lead to innovative strategies that overcome chemoresistance, potentially improving outcomes of cisplatin-based cancer treatments.This comprehensive review provides a multifaceted perspective on the complex mechanisms of ER stress, cisplatin resistance, and their implications in cancer therapy.